Effects of Ouhyul Herbal Acupuncture on Experimentally Induced Endometrosis in Rats - Sang-Suk Yuk; Eun-Mee Lim; Ki-Rok Kwon (Korean Pharmacopuncture Institute, 2006)
Purpose : Endometriosis is characterized by the ectopic growth of uterine tissue in various extrauterine locations. This study examined the macroscopic, hormonal and immunological effects of Ouhyul Herbal Acupuncture(OHA) therapy on rats with experimentally induced endometriosis. Method : Endometrial tissue was implanted in the serosal wall of the small intestine in rats. The rats were divided randomly into an experimental group and control group. The experimental group was treated with OHA on Kwanwon(CV4) three times per week and the control group was administrated normal saline every day. After 6 weeks, the size of the ectopic uterine tissue was estimated and the serum progesterone, estradiol and cytokines(TNF-α, IL-2, IL-4, IL-6, IL-10) concentrations were analyzed. Result : The size of the ectopic uterine tissue in the experimantal group was slightly smaller than that in the control group. The estradiol, IL-4 and IL-6 concentrations were significantly lower and the IL-10 concentration was significantly higher in the serum of the experimental group than in the control group. There was no significant difference in the concentrations of the other cytokines. Conclusion : These results suggest that OHA might be an effective method for treating dometriosis.